Neuromuscular adaptations to 8-week strength training: isotonic versus isokinetic mode - Remaud, A.; Cornu, C.; Guevel, A. (European Journal of Applied Physiology, 2010)
Previous studies attempted to compare the effectiveness of isokinetic and isotonic training. However, they have provided conflicting results. The purpose of this study was to compare the effects of isotonic versus isokinetic standardized concentric strength training programs of the knee extensors on the neuromuscular system. The standardization of these two training programs was ensured by the equalization of the total external amount of work performed and the mean angular movement velocity. Thirty healthy male students were randomly assigned to the isotonic (IT; n = 11), the isokinetic (IK; n = 11) or the control (C; n = 8) group. Both IT and IK groups trained their dominant lower leg 3 sessions/week for 8 weeks on a dynamometer. The IT group exercised using a preset torque of 40% of the maximal voluntary isometric torque at 70° (0° = leg in horizontal position). The IK group exercised at a velocity ranging between 150° and 180° s-1. Isotonic, isokinetic and isometric tests were performed on a dynamometer before and after strength training. Surface electromyographic activity of vastus lateralis, vastus medialis, rectus femoris, semitendinosus and biceps femoris muscles was recorded during the tests. Significant strength increases in both dynamic and static conditions were noticed for IT and IK groups without any significant difference between the two trained groups. Agonist muscle activity also increased with training but no change in antagonist muscle co-activity was observed. The two training methods could be proposed by clinicians and athletic coaches to improve concentric muscle strength in dynamic and static conditions.